Geochemical characterisation of northern Norwegian fjord surface sediments: A baseline for further paleo-environmental investigations - Faust, Johan Christoph; Scheiber, Thomas; Fabian, Karl; Vogt, Christoph; Knies, Jochen (Continental Shelf Research, 2017)
Accepted manuscript version, licensed CC BY-NC-ND 4.0. Published version available at: http://doi.org/10.1016/j.csr.2017.08.015 Norwegian fjord sediments are promising archives for very high resolution records of past environmental changes. Recent investigations of the modern depositional environment within fjords revealed that the accurate quantification of the inputs, sources, and sedimentary preservation of organic and inorganic material is crucial to decipher long term past climate signals in the sedimentary record of a certain fjord. Here, we investigate the elemental composition, bulk mineral assemblage and grain size distribution of forty-one surface sediment samples from a northern Norwegian fjord system. We reveal modern geochemical and sedimentological processes that occur within the Vestfjord, Ofotfjord and Tysfjord. Our results indicate a very heterogeneous sediment supply and intricate sedimentation processes. We propose that this is related to the complex fjord bathymetry, a low hydrodynamic energy environment, differences in the hinterland bedrock composition and a relatively small drainage area causing a rather diffuse freshwater inflow. Moreover, we show that marine carbonate productivity is the main calcite and Ca source in all three fjords.